Comparison of 16S rRNA Sequencing and VITEK 2 Analysis for the Identification of Acinetobacter baumannii Clinical Isolates: A Study from Southwestern Province of Saudi Arabia - Vinod Kumar Basode; Ahmed Abdulhaq; Nader Kameli; Mohammed Uthman A Alamoudi; A Abu Alsayl Zuhair Hussain (Journal of Clinical and Diagnostic Research, 2024)
Acinetobacter baumannii (A. baumannii) is one of the major causes of nosocomial infections in the hospital environment. Even the World Health Organisation (WHO) has designated A. baumannii as a priority pathogen that poses a significant health risk [1]. A. baumannii rapidly develops resistance to antimicrobials, and multidrug-resistant strains have been reported in the literature. As a multidrug-resistant and invasive pathogen, it has been identified as an opportunistic pathogen that causes severe infections such as wound infections, pneumonia, meningitis, septicaemia, and urinary tract infections, resulting in high mortality and morbidity rates. Carbapenem-resistant A. baumannii is a major global public health threat and imposes a greater burden worldwide, including in Saudi Arabia